SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN REKRUTASI CALON KARYAWAN PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS II TELUK BAYUR MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Silfia Andini; Tri Oktaharyadi Putra (Universitas Negeri Padang, 2016)
As we know, in an organizational role of the chie for head ofthe main one is the decision-making.Butit is also possible decision-making is also carried by every level that existed atthe organizational structure. Toassist the heador head inside to take a decision, the computer has an application of Decision Support System. Seeing this that raised the discussion of this thesisis focused on Decision Support System to recruitment the prospective employee's in Kesyahbandaran Office and Authority of Class II Teluk Bayur.With a systemis expected to minimize the occurrence off raudin the selection for the prospective employee's and can optimize decision-making process so that the resulting decision later on right, fast and quality.